Armadillo rodeo - Brett, Jan, 1949- (New York : Putnam's Sons, 1995)
Bo, an adventurous, near-sighted armadillo, leaves his mother and brothers to follow a girl heading to a rodeo wearing new red boots which Bo mistakes for another armadillo.
670
Accelerated Reader AR
Keywords: Rodeos -- Juvenile fiction; Armadillos -- Fiction; Rodeos -- Fiction; Texas -- Fiction